OP0188 The Dose of Glucocorticoids Taken at One Year, but Not The Initial Dose Prescribed, Is An Independent Predictor of Damage Accrual in Lupus Nephritis. (15th July 2016) - El Mourad, A.; Nieuwland-Husson, S.; Depresseux, G.; Houssiau, F.A.
Abstract : Background: Several studies have demonstrated the pivotal role of glucocorticoids (GC) in damage accrual in lupus patients but very few studies were selectively performed in the subgroup of patients suffering from lupus nephritis (LN). Objectives: To define the predictors of damage accrual in a LN population. Methods: We reviewed the files of the 146 patients with biopsy-proven LN included in the Louvain Lupus Nephritis Cohort. The following data were retrieved: demographics, renal pathology, standard renal parameters at baseline and last followup, treatment, renal relapses and SLICC/ACR-DI over time. Results: After a mean followup period of 124 months, 76/146 patients (52%) had some damage, i. e. a SLICC/ACR-DI ≠ 0. The renal, musculoskeletal, cardiovascular and ocular items were the most represented. By univariate analyses, patients with a SLICC/ACR-DI ≠ 0 were older, had a longer followup, took more GC at one year [methylprednisolone (MP): 8.8 mg/d vs 5.7], had suffered from more renal relapses and had develop more renal impairment, including end-stage renal disease. Similar data were obtained if a different SLICC/ACR-DI cutoff value was used (>1 vs ≤1). In a multivariate analysis, using the logistic likelihood ratio test, only 3 variables independently predicted damage, namely the length of followup, the presence of renal relapses and the MP daily dose taken at one year. By contrast, gender, ethnicity, age of onset, standard renal parameters, renal pathology, starting oral MP daily dose, use of IV MP or IV CY did not predict damage. Time to first SLICC/ACR-DI point was statistically shorter, by Kaplan-Meier survival curves, in patients taking ≥4 mg/d of MP after one year of treatment compared to <4 mg/d. Again the initial dose of MP was not influential. Every additional mg/d of MP taken at one year increased the risk of having a SLICC/ACR-DI ≠ 0 by 26% (HR: 1.26; CI: 1.02–1.55). Conclusions: We confirm that more than half of LN patients develop damage over time according to the SLICC/ACR-DI. Interestingly, the dose of GC taken at one year (and not the initial dose prescribed) is an independent predictor of damage accrual. Disclosure of Interest: None declared